The relationship between economic growth, small and medium enterprises and the number of employees in Malaysia using vine copula approach - Mazmira Adan,; Saiful Izzuan Hussain, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper investigates the dynamic linkages of dependency between economic growth, the development of small and medium enterprises (SMEs) in Malaysia represented by SMEs’ value-added, and the number of employees in Malaysia, shown by the total number of SMEs’ employees in Malaysia as an additional variable. A vine copula methods was used to assess the linkage between these three variables by utilizing the panel data sets from 1998-2017. The results confirmed that dependency modeling, using vine copulas, is useful for high dimensional distributions of binding affinity between these variables. Vine copulas provide a versatile and flexible approach to the study. The results show that there is a strong positive correlation among the variables. The dependence between the SMEs’ growth and the total number of employees is the strongest, followed by the dependence between SMEs’ growth and economic growth. This study also found that the interrelation among the variables and reliance structure is also influenced by the country’s economic system and situation.